Pair-Bonding as Inclusion of Other in the Self: A Literature Review - Branand, Brittany; Mashek, Debra; Aron, Arthur (Frontiers in Psychology, 2019)
This article surveys scholarship on the self-expansion model principle of inclusion of other in the self (IOS) as it relates to long-term pair-bonding (i.e., enduring adult romantic monogamous relationships). First, we introduce the concept of IOS and then provide a brief overview of prior research. We then review compelling extensions and findings related to relational concepts such as perspective taking (Bernstein et al., 2015), social comparison (Thai and Lockwood, 2015), self-determination (Weinstein et al., 2016), humor (Treger et al., 2013), and pain contagion (Martire et al., 2013). Next, we explore two recent theoretical directions of the principle—the two-dimensional model of relational self-change (McIntyre et al., 2015) and the perceived inclusion of the other in the self (IOS-perceived) construct (Tomlinson and Aron, 2013). Considering these findings and their relation to pair-bonding, we propose important future directions of the IOS principle of the self-expansion model.